Statistical analysis of low latitude spread F at the American, Atlantic, and Pacific sectors using digisonde observations - Bhaneja, Preeti; Klenzing, Jeff; Pacheco, Edgardo E.; Earle, Gregory D.; Bullett, Terrence W. (Frontiers in Astronomy and Space Sciences, 2024)
Statistical analysis of low latitude spread F is presented for three different longitudinal sectors from Jicamarca (12°S, 76.8°W, −2.5° declination angle) from 2001 to 2016, Ascension Island (7.9°S, 14.4°W, −15.09° declination angle) from 2000 to 2014, Kwajalein (8.71°N, 167.7°E, 7.5° declination angle) from 2004 to 2012. Digisonde data from these stations have been processed and analyzed to study statistical variations of equatorial spread F, a diagnostic of irregular plasma structure in the ionosphere. A new automated method of spread F detection using pattern recognition and edge detection for low latitude regions is used to determine solar and seasonal variation over these three sites. An algorithm has been developed to detect the foF2 and hpF2 parameters and this has been validated by comparisons with manually scaled data as well as with SAMI2 and International Reference Ionosphere models showing good correlation. While significant variation is not observed over the solar cycle, the different longitudes and declination angles contribute to the variations over the seasonal cycle.